Employment relations : industrial relations and human resource management in Australia - Gardner, Margaret Elaine; Palmer, Gill. (South Melbourne : Macmillan Education Australia, 1997)
Studying employment relations. A historical overview of employment relations in Australia. Structuring employment relations. Management policy...
Keywords: Australia; Management; Industry; Personnel management -- Australia; Industrial relations -- Australia